Análise de estabilidade, capabilidade e otimização de um sistema de medição de tonalidade de revestimentos cerâmicos - Dantas, João Batista Cordeiro (2023)
The reduction of defects in the manufacture of ceramic tiles is a challenge for the ceramics industry, seeking to meet the standards and quality criteria required by regulatory agencies and the consumer market. The standardization of colors among the ceramic pieces produced is of fundamental importance and to measure the color variation the spectrophotometer is used. Variation in any process can be associated with the production process itself or with the measurement system used. This work presents a series of analysis studies of measurement system (MSA) of hue of a ceramic production process. Thus, this dissertation aims to minimize the sources of variation in a process for measuring the hue of ceramic tile tiles through stability, capability and optimization studies. A capability analysis was developed evaluating the Cpk index of the production process focusing on the shade variation between ceramic pieces. A repeatability and reproducibility (GR&R) study was carried out and the need for improvements in the measurement system was observed. Thus, a Type 1 study was carried out and optimization was performed using the desirability method based on the Cgk index. The results obtained indicated an optimal setup formed by a template for centralizing the measurement, performing previous cleaning of the part, optical aperture of the spectrophotometer at 6mm and consideration of a value per measurement. In addition, the temperature of the part proved to be a significant factor for measurement variation.